HIGHER ORDER THINKING SKILLS ASSESSMENT (HOTS) - I Wayan Widana (lppm Universitas Negeri Jakarta, 2017)
This study aims to: 1) provide knowledge and understanding to the teachers about the concept and characteristics of the HOTS (Higher Order Thinking Skills) assessment extensively and deep; and 2) improve the skills of the teachers to develop HOTS assessment. To achieve Reviews These objectives, the research literature sourced from journals, reference books, modules, Internet, and other sources such as the print and electronic media that are relevant to the topic HOTS development assessment. Data collected by documentation and observation techniques. The research of data were Analyzed using descriptive exploratory methods. The results of the data analysis are as follows: 1) HOTS assessments are questions or tasks that have Reviews These characteristics: to assess students abilities to analyze, Evaluate, and create based on contextual issues, and are not routine (not familiar); 2) steps compose HOTS items are: a) analyze the KD that can be created HOTS items, b) arrange the blueprint of HOTS items, c) write down the items on the card matter, d) Determine the answer key (multiple choice questions form) or arrange rubric / scoring guidelines (essay form), e) perform qualitative analysis, and f) perform quantitative analysis; 3) the advantage of HOTS assessments are: a) Increase the stundents motivation to learn and b) improve learning outcomes. and f) perform quantitative analysis; 3) the advantage of HOTS assessments are: a) Increase the stundents motivation to learn and b) improve learning outcomes. and f) perform quantitative analysis; 3) the advantage of HOTS assessments are: a) Increase the stundents motivation to learn and b) improve learning outcomes.